High-intensity training in water polo: Swimming versus ball drills - Botonis, P. G.; Malliaros, I.; Arsoniadis, G. G.; Platanou, T. I.; Toubekis, A. G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the acute physiological responses and internal training load of long-interval swimming and water polo-specific drills in high-level water polo players. Methods: A total of 10 water polo players performed both a high-intensity swimming without ball (SW) with intensity corresponding to 90% of their maximum speed previously attained during a 300-m swimming test or a counterattack ball drill (CA). Both SW and CA conditi-ons were designed to provide equal time exposure. Thus, 3 bouts of 4 minutes duration and a 3-minute passive rest were performed in each condition. The players' physiological responses were assessed by continuous monitoring heart rate (HR) during CA and SW as well as by measuring blood lactate at the end of each condition. Rating of perceived exer-tion was recorded at the end of each bout. The Edwards summated HR zones were used to measure internal training load. Results: Both peak and mean HR were similar between SW and CA, and no difference was detected between conditions in the percentage time spent at 90% to 100% of HRpeak. Postexercise blood lactate (8.5 [4.1] vs 11.5 [1.9] mmol/L) and rating of perceived exertion (8.1 [0.8] vs 8.7 [0.5] a.u.) values were lower in CA compared with SW (P<.05). Conclusions: SW compared with CA showed similar cardiac stress but increased anaerobic metabolism activation and higher rating of perceived exertion. Either CA or SW may be both used in training practice as a means to effectively train physical conditioning of water polo players, whereas CA may also facilitate tactical preparation.